THE PHENOMENON OF SELF IN THE CONTEXT OF PSYCHOLOGICAL RESEARCH - Seljuch, Marina G.; Badalyan, Yuliia V.; Zenana, Svetlana R.; Kleme, Viktoriya S.; Pavlova, Ekaterina V. . (International Journal of Psychosocial Rehabilitation, 2020)
The current social transformations increase the importance of a responsible and active attitude of an individual to his personal and professional development thus making the research into the phenomenon of Self vital. The development and realization of Self as a mental phenomenon is, in turn, relevant for the present social situation as the education of the twenty first century relies on the ability of an individual to become the author of his own life.In this context, the paper analyzes the status of the problem of Self in contemporary research, reveals the theoretical basis for the modeling of Self, and proves that it can be viewed as a real complex mental phenomenon. The issue of Self, although not without a research basis, is still important and poses difficulties in defining its characteristics, dynamics and development patterns.The paper addresses Russian and international approaches to studying Self, defining its essence, category, and conceptual irregularities depending on its structure, interpretation of meaning, and psychological content.The analyzed concepts make up a sufficient basis for the modeling of Self, which acts as an integrating factor for all elements of the system of a personality and can be used as a unit of analysis of mental phenomena.